PENGARUH TEACHER EFFICACY TERHADAP MOTIVASI MENGAJAR GURU TINGKAT SEKOLAH MENENGAH PERTAMA (SMP) - Fadia Putri Dianti; Roswiyani Roswiyani (Fakultas Psikologi Universitas Tarumanagara, 2023)
Teaching motivation is the enthusiasm and drive that teachers have to carry out their teaching duties. In fact, there are still teachers who don’t reflect that teachers have a high teaching motivation. One of the factors that can increase the teachers’ teaching motivation is the teacher efficacy. Teacher efficacy is a teacher’s belief in their ability to carry out their duties. This study aims to determine the influence of teacher efficacy on junior high school teachers’ teaching motivation. The type of this research is quantitative research. The data collected used the convenience sampling techniques. Characteristics of the participants in this research are (a) teachers who teach in junior high schools, (b) teaching in public or private schools, (c) aged 20-59 years, (d) male or female, and (e) having a civil servant or non-civil servant status. The measurement tools used in this research are the Teachers’ Sense of Efficacy Scale and the Autonomous Motivation for Teaching Scale. Participants involved in this research are 237 junior high school teachers in Jakarta. The results of this research show that there is a positive and significant relationship between teacher efficacy and the teaching motivation of junior high school teachers, with a value of r = 318. This research found that there is a 10.1% effect of teacher efficacy on junior high school teachers’ teaching motivation. In addition, this research found that there are differences in teacher efficacy based on employment status and the last level of education that teachers have.